2016
DOI: 10.1038/srep35948
|View full text |Cite
|
Sign up to set email alerts
|

High expression of GNA13 is associated with poor prognosis in hepatocellular carcinoma

Abstract: Guanine nucleotide binding protein alpha 13 (GNA13) has been found to play critical roles in the development of several human cancers. However, little is known about GNA13 expression and its clinical significance in hepatocellular carcinoma (HCC). In our study, GNA13 was reported to be significantly up-regulated in HCC tissues, and this was correlated with several clinicopathological parameters, including tumor multiplicity (P = 0.004), TNM stage (P = 0.002), and BCLC stage (P = 0.010). Further Cox regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…GNA13 has recently been shown to be highly expressed in a variety of human malignancies, including gastric carcinoma, liver carcinoma, and lymphoma, and is positively correlated with tumor progression. 15,[20][21][22] However, the role of GNA13 in CRC is unknown. Our study showed that the upregulation of GNA13 in CRC tissues was related to an exacerbated tumor grade and shorter survival.…”
Section: Discussionmentioning
confidence: 99%
“…GNA13 has recently been shown to be highly expressed in a variety of human malignancies, including gastric carcinoma, liver carcinoma, and lymphoma, and is positively correlated with tumor progression. 15,[20][21][22] However, the role of GNA13 in CRC is unknown. Our study showed that the upregulation of GNA13 in CRC tissues was related to an exacerbated tumor grade and shorter survival.…”
Section: Discussionmentioning
confidence: 99%
“…Their downstream signaling cascades are transduced through G‐Alpha12 (GNA12) and G‐Alpha13 (GNA13) subunits constituting the subfamily of heterotrimeric G‐proteins. Indeed, invasion and metastasis have been attributed to GNA proteins in many cancer types . Some findings reported that GNA13 is highly upregulated in the aggressive form of breast cancer cells and restoration of GNA13 activity has been shown to enhance the progression and invasion characteristics of prostate and gastric cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Gα 12/13 , also known as gep proto-oncogenes, are often overexpressed in cancers, including breast 12 , prostate 13 , and liver 14 cancers. They serve as prognostic factors, and high expression of Gα 12/13 is associated with poor prognosis for patients 15 , 16 . The members of the Gα 12/13 family have been recently identified as direct or indirect regulators of systemic energy metabolism.…”
Section: Gpcr–g Protein Pathways In Metabolic Diseasesmentioning
confidence: 99%